2003
DOI: 10.1182/blood-2002-10-3190
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 down-regulates expression of chemokine stromal cell–derived factor-1: functional consequences in cell migration and adhesion

Abstract: Chemokine stromal cell-derived factor-1 (SDF-1) is expressed by bone marrow (BM) stromal cells and plays key roles in BM cell migration. Modulation of its expression could affect the migratory capacity of cells trafficking the BM, such as hematopoietic progenitor and leukemic cells. Transforming growth factor-beta1 (TGF-beta1) is present in the BM environment and constitutes a pivotal molecule controlling BM cell proliferation and differentiation. We used the BM stromal cell line MS-5 as a model to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
74
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 51 publications
(42 reference statements)
9
74
0
Order By: Relevance
“…The findings extend data that were reported by Wright et al in the murine BMSC cell line MS-5. The authors described an early inhibitory effect of TGFB1 on the promoter of the CXCL12 gene which was counteracted by CXCL-12 mRNA increments after 12 h. 32 In the primary hBMSC culture, we observed a suppressive effect of TGFB1 on CXCL12 levels which was maintained for at least 24 h and was, therefore, long-lasting (data not shown). We speculated that the TGFB1-associated effect is pronounced by the activity of inhibitory miRNAs.…”
mentioning
confidence: 51%
“…The findings extend data that were reported by Wright et al in the murine BMSC cell line MS-5. The authors described an early inhibitory effect of TGFB1 on the promoter of the CXCL12 gene which was counteracted by CXCL-12 mRNA increments after 12 h. 32 In the primary hBMSC culture, we observed a suppressive effect of TGFB1 on CXCL12 levels which was maintained for at least 24 h and was, therefore, long-lasting (data not shown). We speculated that the TGFB1-associated effect is pronounced by the activity of inhibitory miRNAs.…”
mentioning
confidence: 51%
“…Myeloma cells increase Th3 cytokine response by secreting TGFβ1, which causes defective Th1 and Th2 cytokine responses, therefore a significant suppression of the immune system is seen (26). TGFβ1 is present in the bone marrow (BM) environment and constitutes a pivotal molecule controlling BM cell proliferation and differentiation (27). Study in MM showed that IL-2 and IL-4 levels in patients were lower than those in the normal controls, whereas TGFβ1 level were higher than that in controls (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…78 Conversely, the expression of SDF-1 was found to be downregulated by steroids, 79 G-CSF 80 and transforming growth factor (TGF)-b1. 81 On the other hand, it was reported that low levels of TGF-b1 can modulate SDF-1 responsiveness of CD34 þ cells and thus facilitate SDF-1-mediated retention and nurturing of stem/progenitor cells in BM. 82 As a strong correlation exists between chronic inflammation and tumor progression/metastasis, inflammation-driven expression of SDF-1 may also play an important role in dissemination/ metastasis of CSC.…”
Section: Cancer Cells Express Cxcr4mentioning
confidence: 99%